2018
DOI: 10.5811/westjem.2018.8.39336
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid in Civilian Trauma Care in the California Prehospital Antifibrinolytic Therapy Study

Abstract: IntroductionHemorrhage is one of the leading causes of death in trauma victims. Historically, paramedics have not had access to medications that specifically target the reversal of trauma-induced coagulopathies. The California Prehospital Antifibrinolytic Therapy (Cal-PAT) study seeks to evaluate the safety and efficacy of tranexamic acid (TXA) use in the civilian prehospital setting in cases of traumatic hemorrhagic shock.MethodsThe Cal-PAT study is a multi-centered, prospective, observational cohort study wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 30 publications
(59 reference statements)
0
64
0
1
Order By: Relevance
“…Given the complex maxillofacial regional bony and vascular anatomy relationships, such control techniques are challenging in the trauma setting prior to operative exploration. This case further highlights the potential survival benefits demonstrated in the use of TXA in civilian vascular trauma [18][19].…”
Section: Discussionmentioning
confidence: 72%
“…Given the complex maxillofacial regional bony and vascular anatomy relationships, such control techniques are challenging in the trauma setting prior to operative exploration. This case further highlights the potential survival benefits demonstrated in the use of TXA in civilian vascular trauma [18][19].…”
Section: Discussionmentioning
confidence: 72%
“…Of 96 articles included, the overwhelming majority (90, 94%) were observational with a few (6, 6%) being interventional in design (Table 2 ) [ 69 , 78 , 85 , 88 , 95 , 98 ]. The six interventional studies evaluated the effects of prehospital blood product transfusion (plasma and packed red blood cells), and TXA administration on mortality, and used time (from injury to intervention) as a covariate.…”
Section: Resultsmentioning
confidence: 99%
“…Prehospital time was used as an outcome measure in 10 (10%) studies [ 2 , 61 , 62 , 74 , 75 , 83 , 85 , 88 , 94 , 98 ]. Four of these studies evaluated the time resultant from one of the following independent factors: prehospital endotracheal intubation, chest tube insertion, needle thoracostomy, tourniquet application, cricothyroidotomy, and advanced cardiac life support [ 61 , 74 , 75 , 83 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies have not identified an increase in incidence of VTE associated with TXA, others have found TXA to be an independent risk factor for increased incidence of VTE. 11,12,14,[17][18][19] Thus, there is a need to continue to further evaluate the safety of TXA use within the hospital trauma setting.…”
Section: Introductionmentioning
confidence: 99%